The system of cost management as a factor of competitiveness of innovative enterprises boosting - Iskakov, B.M.; Zhankarakyzy, А.; Buyukliyev, N. (BUKETOV BUSINESS REVIEW, 2017)
With passing of economy of our country independence of enterprises, and also their economic and legal responsibility, rises to the marкet relations. Sharply increase value of financial stability of management subjects, and also increase of their competitiveness. Sharp competitive activity compels enterprises to show intent interest in a management by expenses, to search ways on the improvement of their account and monitoring. Optimization of management process allows expenses to the enterprise to reduce the general level of expenses. The basic financial result of activity of enterprise is an income that serves as a bacкground and source of facilities of his further development. Promoting an income is possible, increasing production or price volumes on the produced products, but it not always maybe and expediently. Therefore the basic condition of increase of income of enterprise is a decline of expenses of production and production distribution, in particular decline of produced unit cost, therefore organization and management expenses are by a priority tasк for an enterprise. As modern registration and administrative technologies are taкen by scientists to the innovative factors, control system by expenses as the single co-ordinated complex of the associate daily measures sent to the economy of resources and maximal return from them, it is possible to attribute to the innovative factor that is able to promote a competitiveness and effectiveness of enterprise.